Genome sequencing of linezolid-resistant Streptococcus pneumoniae mutants reveals novel mechanisms of resistance - Feng, Jie; Lupien, Andréanne; Gingras, Hélène; Wasserscheid, Jessica; Dewar, Ken; Légaré, Danielle; Ouellette, Marc (Genome Research, 2009)
Linezolid is a member of a novel class of antibiotics, with resistance already being reported. We used whole-genome sequencing on three independent Streptococcus pneumoniae strains made resistant to linezolid in vitro in a step-by-step fashion. Analysis of the genome assemblies revealed mutations in the 23S rRNA gene in all mutants including, notably, G2576T, a previously recognized resistance mutation. Mutations in an additional 31 genes were also found in at least one of the three sequenced genomes. We concentrated on three new mutations that were found in at least two independent mutants. All three mutations were experimentally confirmed to be involved in antibiotic resistance. Mutations upstream of the ABC transporter genes spr1021 and spr1887 were correlated with increased expression of these genes and neighboring genes of the same operon. Gene inactivation supported a role for these ABC transporters in resistance to linezolid and other antibiotics. The hypothetical protein spr0333 contains an RNA methyltransferase domain, and mutations within that domain were found in all S. pneumoniae linezolid-resistant strains. Primer extension experiments indicated that spr0333 methylates G2445 of the 23S rRNA and mutations in spr0333 abolished this methylation. Reintroduction of a nonmutated version of spr0333 in resistant bacteria reestablished G2445 methylation and led to cells being more sensitive to linezolid and other antibiotics. Interestingly, the spr0333 ortholog was also mutated in a linezolid-resistant clinical Staphylococcus aureus isolate. Whole-genome sequencing and comparative analyses of S. pneumoniae resistant isolates was useful for discovering novel resistance mutations.